The notification submitted by the President of the Republic between continuity and effectiveness (A study in the light of the Algerian constitution). - litouche, Dalila (Milev Journal of Research and Studies, 2021)
The President of the Republic exercises the right of notification as he is considered the head of the executive authority, and he continues through the Algerian constitutions in his exercise of the idea of the extent to which it is done according to what is required and required by the popular will and the preservation of rights and freedoms, as well as the extent to which he achieves the balance between the three authorities, especially as it is an additional measure of his broad powers Constitutionally granted to him, although it emerges through most of the amendments that granting notification in every stage of amendment and development of Algerian constitutions to the latter in real terms does not fulfill the requirements and aspirations of the people and remains a tool for the hegemony of the executive authority.